2013
DOI: 10.1111/jar.12049
|View full text |Cite
|
Sign up to set email alerts
|

How Effective is the Cognitive Interview When Used with Adults with Intellectual Disabilities Specifically with Conversation Recall?

Abstract: The findings suggest that the CI can enable adults with intellectual disability to provide a fuller picture about an experienced event. Implications of this research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…in a related vein, individuals in both ID groups also provided fewer details than did their MA matches. This finding is in accordance with those in previous studies, which have found the retrieval skills of ID individuals to be less effective, detracting from the completeness of their witnessing reports (Clarke et al, 2013; Milne et al, 1999; Perlman et al, 1994; Ternes & Yuille, 2008). But, although previous findings lead one to expect individuals with moderate ID to provide fewer details in comparison to MA matches (Agnew & Powell, 2004; Brown et al, 2015, 2012; but see Henry & Gudjonsson, 2003), they also pointed to a similarity between those with mild ID and their MA matches in detail production (Brown et al, 2015, 2012; Henry & Gudjonsson, 2003; but see Agnew & Powell, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…in a related vein, individuals in both ID groups also provided fewer details than did their MA matches. This finding is in accordance with those in previous studies, which have found the retrieval skills of ID individuals to be less effective, detracting from the completeness of their witnessing reports (Clarke et al, 2013; Milne et al, 1999; Perlman et al, 1994; Ternes & Yuille, 2008). But, although previous findings lead one to expect individuals with moderate ID to provide fewer details in comparison to MA matches (Agnew & Powell, 2004; Brown et al, 2015, 2012; but see Henry & Gudjonsson, 2003), they also pointed to a similarity between those with mild ID and their MA matches in detail production (Brown et al, 2015, 2012; Henry & Gudjonsson, 2003; but see Agnew & Powell, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…As opposed to studies of ID children, eyewitness studies of ID adults have not employed MA or CA matches but rather comparison groups made of TD adults. These studies have found that, like children with mild ID, adults with mild ID do not provide as many details as do TD counterparts (Clarke, Prescott, & Milne, 2013; Milne, Clare, & Bull, 1999; Perlman, Ericson, Esses, & Isaacs, 1994; Ternes & Yuille, 2008). As for the accuracy of their statements, results have been mixed: Whereas some studies have found adults with mild ID to be as accurate as are TD counterparts in some or all parts of the interview (Perlman et al, 1994; Ternes & Yuille, 2008), others have found them to be less accurate (Clarke et al, 2013; Milne et al, 1999).…”
mentioning
confidence: 99%
“…It seems that once memory is exhausted in a free recall, an open prompt to extend a free recall may not be a useful tool for acquiring high-quality information. Indeed, past research examining the efficacy of the cognitive interview often found that second and third retrieval attempts had lower accuracy rates than an initial free recall (e.g., Clarke, Prescott, & Milne, 2013;. More recent research has also found this effect (see Kontogianni et al, 2020).…”
Section: Discussionmentioning
confidence: 98%